Burnout Among Filipino Occupational Therapists: A Mixed Methods Analysis - Rod Charlie Delos Reyes (Scholarworks @ WMU, 2018)
Background: There is a shortage of practicing occupational therapists in the Philippines, with approximately one Filipino occupational therapist per 30,000 stakeholders. One of the possible consequences is the experience of burnout among therapists. Method: A two-phase mixed methods study using a sequential explanatory approach was used. The first phase involved the administration of the Maslach Burnout Inventory - Human Services Survey (MBI-HSS) with a survey questionnaire that supplied demographic and work-related factors through an online platform. The results were analyzed using frequency distribution and measures of central tendency. Relationships were analyzed using Spearman's Rho and Cramer's V. The second phase involved a focus group discussion and a series of in-depth interviews. Directed content analysis was conducted to form themes from the results. Results: A response rate of 24.7% was achieved. The results indicated that several conditions influenced burnout for Filipino occupational therapists. These included an age range of 24 to 29 years of age, being unmarried, working during the early years of practice, and working longer hours. Conclusion: The Filipino occupational therapists in this study experienced being drained from different sources of pressure, including their own and society's expectations. This appeared to lead to at least some level of burnout and a decrease in creativity in practice.